2021
DOI: 10.3892/ol.2021.12994
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear polymorphism at the 8q24 region is associated with improved survival time and chemo‑response in high‑grade serous ovarian cancer

Abstract: The 8q24 chromosomal region is strongly associated with an increased risk of ovarian cancer. One single nucleotide polymorphism that is associated with ovarian cancer in this region is rs6983267, located within the long non-coding RNA colon cancer associated transcript 2 (CCAT2). The aim of the present study was to assess the association between rs6983267 and clinical outcomes in patients with high-grade serous ovarian cancer (HGSOC). The present retrospective genetic association study utilized Sanger sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…51 As an important lncRNA, MYCBP2-AS1 is associated with improved survival time and chemoresponse in high-grade serous ovarian cancer. 52 Despite some research on how MYCBP-related lncRNAs may contribute to human diseases, the exact roles of GJA9-MYCBP in the pathophysiology of leukemia are still blanketed in mystery. Herein, we showed that in ALL samples, GJA9-MYCBP was upregulated in patients' samples compared to the healthy ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 As an important lncRNA, MYCBP2-AS1 is associated with improved survival time and chemoresponse in high-grade serous ovarian cancer. 52 Despite some research on how MYCBP-related lncRNAs may contribute to human diseases, the exact roles of GJA9-MYCBP in the pathophysiology of leukemia are still blanketed in mystery. Herein, we showed that in ALL samples, GJA9-MYCBP was upregulated in patients' samples compared to the healthy ones.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of MYCBP promoted the invasion and migration of gastric cancer cells 51 . As an important lncRNA, MYCBP2‐AS1 is associated with improved survival time and chemo‐response in high‐grade serous ovarian cancer 52 . Despite some research on how MYCBP‐related lncRNAs may contribute to human diseases, the exact roles of GJA9‐MYCBP in the pathophysiology of leukemia are still blanketed in mystery.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of MYCBP promoted the invasion and migration of gastric cancer cells [51]. As an important lncRNA, MYCBP2-AS1 is associated with improved survival time and chemoresponse in high-grade serous ovarian cancer [52]. Despite some research on how MYCBP-related lncRNAs may contribute to human diseases, the exact roles of GJA9-MYCBP in the pathophysiology of leukemia are still blanketed in mystery.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies showed that the lncRNA CCAT2 rs6983267 polymorphism is significantly correlated with an increased possibility of ovarian cancer(J. Han et al, 2017) (Ikoma et al, 2021) and an increased risk of prostate cancer(M. Zhu et al, 2017). Further research discovered that rs6983267 had a slight connection with breast cancer (He et al, 2017).…”
Section: Genetic Susceptibility To Recurrent Miscarriagementioning
confidence: 99%